Sex differences in a double-blind randomized clinical trial with minocycline in treatment-resistant depressed patients: CRP and IL-6 as sex-specific predictors of treatment response - Giulia Lombardo; Maria Antonietta Nettis; Caitlin Hastings; Zuzanna Zajkowska; Nicole Mariani; Naghmeh Nikkheslat; Courtney Worrell; Daniela Enache; Anna McLaughlin; Melisa Kose; Anna Bogdanova; Luca Sforzini; et al. (Brain, Behavior, & Immunity - Health, 2022)
Background: Inflammation is a well-known risk factor for depression. Specifically, patients who do not respond to antidepressant treatment show higher levels of inflammatory biomarkers compared with responders. Thus, several studies have investigated the efficacy of anti-inflammatory add-on treatment in this population. However, major depressive disorder is more prevalent in females than in males, with sex differences present in antidepressant treatment response and in immune system regulation. To explore sex differences in inflammatory profiles and treatment responses, we investigated a cohort of patients with treatment resistant depression (TRD), for which they received an adjunctive, anti-inflammatory treatment with minocycline – the Minocycline in Depression (MINDEP) study. Methods: The MINDEP study is a 4-week double-blind, randomised, placebo-controlled clinical trial (stratified by sex) with 39 TRD participants, which demonstrated the efficacy of minocycline, an antibiotic with anti-inflammatory properties, in TRD patients with major depressive disorder (MDD) and evidence of low-grade inflammation measured with C-reactive protein (CRP) ≥ 3 mg/L. In these secondary analyses, we investigated the differential effects of minocycline in females (N = 22, 10 randomised to minocycline and 12 randomised to placebo) and in males (N = 17, 8 randomised to minocycline and 9 randomised to placebo) on changes in depressive symptoms (Δ- Hamilton Rating Scale for Depression (HAMD)-17), taking also into consideration CRP levels (CRP ≥3 mg/L vs. CRP <3 mg/L). Additionally, we investigated the role of serum IL-6 in predicting treatment response to minocycline, using sex-specific medians of IL-6, in novel exploratory analyses. Results: Sex differences in Δ-HAMD-17 indicate that only females (F = 10.49, p = 0.005), but not males (F = 1.64, p = 0.22), presented an effect of CRP levels on the response to minocycline. Also, we detected sex differences in the relationship between serum CRP and IL-6 levels: CRP was strongly correlated with IL-6 in females (Spearman's ρ = 0.658, P < 0.001) but not in males (ρ = 0.007, p = 0.979). Exploratory analyses found that IL-6 was indeed a better predictor of response than minocycline than CRP, as we found an interaction between study arms and IL-6 groups (above and below the IL-6 sex-specific median) in females (F = 4.435 p = 0.050) and, at trend statistical level, in males (F = 4.258 p = 0.060). Moreover, Δ-HAMD-17 was numerically comparable in the two high-IL-6 group taking minocycline (females, mean 9.20 ± SD 7.80; males, mean 8.80 ± SD 5.97), confirming that high IL-6, differently from high CRP, identified responders to minocycline both in males and females. Conclusion: Our findings highlight the need of sex-specific inflammatory biomarkers in predicting antidepressant response to anti-inflammatories in TRD patients, with the possibility of CRP being a relevant predictor of treatment response only for females, and IL-6 being relevant for both sexes.